Suicidal Tendency in Martin Sharp’s Depression of Nick Hornby’s A Long Way Down - Ahmad Dientara, Fahrurozy; Tri Wedawati, Mamik; Dhika Arif Rizqan, Muhammad (Udayana Journal of Social Sciences and Humanities; Vol 3 No 2 (2019): UJoSSH, September 2019DO - 10.24843/UJoSSH.2019.v03.i02.p09, 2020)
Suicidal ideation, also known as suicidal thoughts or suicidal tendencies, concerns one thought about suicide. A Long Way Down tells about four characters that need to be done on New Year's Eve at the Topper's House building, London. The focus of this study on one of the main characters in this novel named Martin Sharp. There are two questions in this study: How is the tendency of self-murder to be described in A Long Way Down? and What is the socio-cultural influence on suicidal tendency of Martin Sharp? The study aims to reflect the desire to kill themselves in novel works and what socio-cultural things that causes of the desire to kill themselves. The core data from this study were taken from soliloquy and the thought narrative of Martin Sharp. Data were analyzed using Emile Durkheim’s theory of suicide types. The results of this study showed that there are those who prove themselves from Martin Sharp causing by three socio-cultural issues that surround it: his status as a man who is middle-aged in England, family relations, and social pressure. The thought of self-killing from Martin Sharp was categorized as egoistic self-murder.